2012
DOI: 10.1155/2012/589494
|View full text |Cite
|
Sign up to set email alerts
|

Host Susceptibility toBrucella abortusInfection Is More Pronounced in IFN-γknockout than IL-12/β2-Microglobulin Double-Deficient Mice

Abstract: Brucella abortus is a facultative intracellular bacterial pathogen that causes abortion in domestic animals and undulant fever in humans. IFN-γ, IL-12, and CD8+ T lymphocytes are important components of host immune responses against B. abortus. Herein, IFN-γ and IL-12/β2-microglobulin (β2-m) knockout mice were used to determine whether CD8+ T cells and IL-12-dependent IFN-γ deficiency would be more critical to control B. abortus infection compared to the lack of endogenous IFN-γ. At 1 week after infection, IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 31 publications
4
53
0
1
Order By: Relevance
“…+ T cells in the primary control of Brucella infection (16,35,(41)(42)(43). We confirmed this key role in our i.n.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…+ T cells in the primary control of Brucella infection (16,35,(41)(42)(43). We confirmed this key role in our i.n.…”
Section: Discussionsupporting
confidence: 84%
“…infectious model, the absence of IFN-gR was associated with a drastic alteration in the granuloma composition, which appeared to primarily contain neutrophils, and a lack of tissue confinement of Brucella, as demonstrated by the high levels of bacteria observed in the blood of IFN-gR 2/2 mice during chronic infection but not during the early phases of infection. In summary, our results strongly suggest that the protective role of IFN-g against Brucella infection is primarily limited to the chronic phase of infection and may even have been overestimated based on the exceptional mortality associated with IFN-g deficiency (41,43). IFN-g is clearly crucial to late Brucella control in all organs, but is not sufficient, because we observed, in an i.p.…”
Section: Discussionmentioning
confidence: 74%
“…abortus ⌬mfp induces IFN-␥ production similar to that of the vaccine strains S19 and RB51. IFN-␥ is required for the bactericidal activity of macrophages and is a key cytokine in immunity against Brucella (24,25). Therefore, we investigated the IFN-␥ production of splenocytes in mice previously immunized with the ⌬mfp::kan or ⌬omp19::kan strain in response to challenge with the B. abortus wild-type strain.…”
Section: Resultsmentioning
confidence: 99%
“…A Th1 cell-dominant response is required for protection against Brucella infection (25,30). Therefore, the induction of a Th1 profile can be used as an indicator of potential Brucella vaccine efficacy in the preliminary screenings of potential candidates (12).…”
Section: Discussionmentioning
confidence: 99%
“…This IFN-γ priming effect has been increasingly implicated in the immune response to several infectious diseases, including viral, bacterial, and parasitic diseases [12][13][14]. For brucellosis, the crucial role of IFN-γ was recognized, as it was shown that IFN-γ knockout mice died due to B. abortus infection and IFN-γ producing CD4+ T-cells from infected donors were able to protect the recipient mice against challenge with B. abortus [15]. IFN-γ was induced by reactive nitrogen intermediates and reactive oxygen intermediates after mouse macrophages were activated [16].…”
Section: Discussionmentioning
confidence: 99%